2011
DOI: 10.3109/14767058.2011.622009
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric and perinatal outcome in women with twin pregnancy and gestational diabetes

Abstract: The presence of GDM in twin pregnancy was associated with a higher risk of hypertensive complications, prematurity and macrosomia, but significantly reduces the risk of SGA infants. Prematurity was related to the presence of other associated pregnancy complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
25
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 27 publications
16
25
2
Order By: Relevance
“…In terms of infant characteristics, the number of large for gestational age infants (using twin charts) decreased with a change in gestational diabetes screening, and there was no association found between gestational diabetes and large for gestational age. In some studies of twin pregnancies, women with gestational diabetes have been found to have higher rates of large for gestational age infants and Caesarean section . By contrast, an Israeli cohort study of twin pregnancies found no difference in Caesarean section rates in women with gestational diabetes compared with no gestational diabetes and a reduction in perinatal mortality in infants born to women with gestational diabetes , which is consistent with our study.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In terms of infant characteristics, the number of large for gestational age infants (using twin charts) decreased with a change in gestational diabetes screening, and there was no association found between gestational diabetes and large for gestational age. In some studies of twin pregnancies, women with gestational diabetes have been found to have higher rates of large for gestational age infants and Caesarean section . By contrast, an Israeli cohort study of twin pregnancies found no difference in Caesarean section rates in women with gestational diabetes compared with no gestational diabetes and a reduction in perinatal mortality in infants born to women with gestational diabetes , which is consistent with our study.…”
Section: Discussionsupporting
confidence: 91%
“…Women with twin pregnancies and gestational diabetes were found to have higher rates of hypertensive disorders, which is consistent with other studies . However, despite increased rates of gestational diabetes diagnoses with a change in gestational diabetes screening, there was no decrease in hypertensive disorders.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Many population-based studies evaluating women with pregestational diabetes mellitus (DM) have reported large-for-gestational age (LGA) rates as high as 28-45% [1,3,4] in both type 1 and 2 DM [5]. Among women with gestational DM, the percentage of neonates diagnosed as LGA is also increased by 15-20% [6,7], even in twin pregnancies [8], and the rate of SGA is much lower, around 3 and 2% for type 1 and 2 DM, respectively [5]. …”
Section: Introductionmentioning
confidence: 99%